2021
DOI: 10.1089/aid.2020.0197
|View full text |Cite
|
Sign up to set email alerts
|

Weight and Body Mass Index Change After Switching to Integrase Inhibitors or Tenofovir Alafenamide Among Women Living with HIV

Abstract: Weight and body mass index (BMI) change was assessed among women after switch to integrase inhibitors (INSTIs) and/or tenofovir alafenamide (TAF). From 2006 to 2019, 1,458 women living with HIV enrolled in the Women's Interagency HIV Study and on antiretroviral therapy (ART) with ‡1 study visit before and after switching to INSTIs and/or TAF were included. Weight and BMI were compared pre-and postswitch to INSTI (by class and type) and/or TAF using multivariable linear mixed effects models; all models were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Furthermore, almost one-third of women (30% of WLWH, 30% of HIV-) had clinically-relevant depressive symptoms (28-33). Among WLWH, certain antiretroviral therapies (ARTs) may cause body weight gain and/or body fat redistribution and potentially in uence NP (34)(35)(36) and increase the vulnerability of WLWH to cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, almost one-third of women (30% of WLWH, 30% of HIV-) had clinically-relevant depressive symptoms (28-33). Among WLWH, certain antiretroviral therapies (ARTs) may cause body weight gain and/or body fat redistribution and potentially in uence NP (34)(35)(36) and increase the vulnerability of WLWH to cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Findings reported greater weight gain in patients treated with dolutegravir compared to efavirenz in clinical trials in Africa: leading to concerns about longterm effects of obesity with lifelong antiretroviral therapy (ART) [4,5]. Furthermore, recent studies (2021) have reported an association between weight gain and dolutegravir in PHIV, most often in Black ethnic groups and women [6,7]. Although the mechanisms whereby dolutegravir cause weight gain remain unclear; it is hypothesized that the weight gain may be multifactorial in nature: with genetic predisposition, HIV-related factors, the 'return to health' weight gain and demographic factors all contributing.…”
mentioning
confidence: 99%
“…Among women living with HIV (WLWH), increases in body weight and body mass index (BMI, kg/m 2 ) have been observed after switching to the antiretroviral therapies (ART) - Integrase Inhibitors (INSTI) and/or Tenofovir Alafenamide (TAF) [ 1 , 2 ]. This has broad implications for the HIV aging process and occurrence of later-life disease.…”
mentioning
confidence: 99%
“…Consequently, we can expect more ART-related cardiovascular and cerebrovascular sequelae, as well as polypharmacy to control both HIV infection and vascular risk. The paper by Lahiri, et al [ 1 ] offers insights into the role of ART, specifically INSTI and TAF, on simple clinical measures of body weight and BMI.…”
mentioning
confidence: 99%
See 1 more Smart Citation